Multicultural Islamic Education: An Analysis Of The Picture Of A Multicultural Society - Suprianto, Miki; Widiyanti, Zelmi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
Indonesian society is a group of people who are pluralistic living side by side with each other, with differences in ethnicity, language, culture and religion. Therefore, this study aims to see the picture of a multicultural society in Indonesia from the emergence of multiculturalism, a multicultural picture of Indonesian society and its understanding of multiculturalism and its relationship with multicultural Islamic education. This study uses a qualitative descriptive approach and data collection using the Literature study method. The Reseacrh data library method or Literature study is research that is carried out not in the field but by analyzing the latest articles and books. Based on articles or data sources analyzed by researchers, a picture of a multicultural society was found, with the diversity that existed, the community remained in a condition of mutual respect and understanding of each other. so that there is no discrimination against certain ethnicities, cultures, languages and religions. We must cultivate an attitude of mutual respect and mutual respect within the framework of the nation's ideology. The difference in inevitability that God has revealed to humans, bhineka tunggal ika is a derivative entrusted to us by our ancestors, this is what shapes our understanding of multiculturalism in society and nation, so that the value of religious moderation grows in the midst of society.